The Effect of Testosterone on Liver Tissue and Lipid Profile in Female Rats (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Androgenic and anabolic action of testosterone mediated through androgen receptor, which have been documented to have significant biological actions in bone, muscle, prostate, adipose tissue and the reproductive, cardiovascular, immune, neural and haemopoietic systems.Aim: Evaluate the action of testosterone on liver histology and lipid profile (cholesterol, triglyceride, LDL, HDL and VLDL).Materials and Methods: Adult female wistar rat (no. 12) and weight (180-200 g) was housed in stain steel cages. Six rats were divided into two groups control group given propylene glycol as vehicle while treated group give testosterone propionate subcutaneous with 100mg/kg dose dissolve in propylene glycol for 30 days. Live histology examination and lipid profile assessment were conducted to compare the differences and the effect of the testosterone.Results: There was no significant differences in all parameters of cholesterol, triglyceride, low-density lipoprotein, high-density lipoprotein and very low-density lipoprotein, while the histology of treated group showed dilatations of the hepatic sinusoids which led to increase pressure of the hepatic biliary system, with fatty changes and dysplasia of hepatocytes.Conclusion: Testosterone plays an important role in aging by increasing hepatic glycogen stores and alteration of hepatic tissues.